Harry Langdon : King of Silent Comedy - Oldham, Gabriella; Langdon, Mabel (Book collections on Project MUSE., 2017)
Among silent film comedians, three names stand out -- Charlie Chaplin, Buster Keaton, and Harold Lloyd -- but Harry Langdon indisputably deserves to sit among them as the fourth "king." In films such as The Strong Man (1926) and Long Pants (1927) , Langdon parlayed his pantomime talents, expressive eyes, and childlike innocence into silent-era stardom. This in-depth biography, which features behind-the-scenes accounts and personal recollections compiled by Langdon's late wife, provides a full and thoughtful picture of this multifaceted entertainer and his meteoric rise and fall. Authors Gabriella Oldham and Mabel Langdon explore how the actor developed and honed his comedic skills in amateur shows, medicine shows, and vaudeville. Together they survey his early work on the stage at the turn of the twentieth century as well as his iconic routines and characters. They also evaluate his failures from the early sound period, including his decision to part ways with director Frank Capra. Despite his dwindling popularity following the introduction of talkies, Langdon persevered and continued to perform in theater, radio, and film -- literally until his dying day -- leaving behind a unique and brilliant body of work. Featuring never-before-published stories and photos from his immediate family, this biography is a fascinating and revealing look at an unsung silent film giant.